POVERTY REDUCTION in CENTRAL JAVA PROVINCE INDONESIA THROUGH THE TOURISM SECTOR - Agus, Irwan; Priadana, Sidik; Karno, K; Sari, Indah Purnama (Journal of Economic Development, Environment and People, 2022)
This research studies the influence of the tourism sector GRDP on poverty in Central Java Province. The research uses quantitative methods with linear regression techniques using time series data. The data for this research is secondary data that spans 15 years, starting from 2005 to 2019, which is represented in semester data. The total sample used is 30 samples. After the Classical Assumption Test was performed then the data analyzed using Cobb-Douglas linear regression model with Ordinary Least Square (OLS) technique. The research results showed that Tourism Sector GRDP had a significant negative effect on poverty. Based on that tourism sector can be one of the most potential approaches to be developed for alleviating poverty in Central Java Province.